Peran Guru Bimbingan Konseling (BK) dalam Membentuk Karakter Siswa Kristen - Erna Alinda Hendrika Ottu; Reni Triposa (Sekolah Tinggi Teologi Nusantara, 2021)
A guidance teacher or counselor is a person who is professionally trained, namely a mentor / counselor who has an academic education and has experience in professional skills training. The task of the counseling guidance teacher is a teacher who has full duties and responsibilities, authority and rights in guidance activities for a number of students. Supervising teachers must be able to carry out their duties and be entrusted with implementing the guidance service program, the implementation of activities carried out in accordance with the prepared plans in the fields of personal, social, learning, career, religious life and family life. The problems experienced by counseling guidance teachers today are difficult. to shape the character of students during adolescence, this is due to the influence of the times. Using descriptive qualitative methods, it can be concluded that the role of counseling guidance teachers in shaping the character of Christian students can be studied as counseling teachers can understand and interpret the definition of Counseling Guidance, and can provide the Counseling Guidance program as an effort to build character. Because it is the function of the counseling teacher. So that the counseling guidance teacher can achieve the objectives of counseling guidance and the nature of Christian religious education in providing the basis that there is Character Building for children of students which is carried out through character building through Christian values. Abstrak:Guru bimbingan atau konselor merupakan seorang yang terlatih secara profesional, yaitu guru pembimbing/konselor yang memiliki pendidikan secara akademik serta memiliki pengalaman latihan-latihan ketrampilan secara profesional. Tugas guru bimbingan konseling merupakan guru yang mempunyai tugas dan tanggung jawab, wewenang dan hak secara penuh dalam kegiatan bimbingan terhadap sejumlah peserta didik. Guru pembimbing harus mampu menjalankan tugasnya dan amanah dalam melaksanakan program pelayanan bimbingan, pelaksanaan kegiatan yang dilakukan sesuai dengan perencanaan yang telah dipersiapkan pada bidang bimbingan pribadi, sosial, belajar, karier, kehidupan keberagamaan dan kehidupan berkeluarga. Masalahnya yang dialami guru bimbingan konseling saat ini adalah sulit untuk membentuk karakter siswa pada masa remaja, hal ini dikarenakan pengaruh dari perkembangan zaman. Penelitian ini menggunakan metode Pustaka dengan pendekatan kualitatif deskritif dapat disimpulkan bahwa peran Guru bimbingan konseling dalam membentuk karakter siswa Kristen dapat dikaji sebagaimana guru bimbingan konseling dapat mengerti dan memaknai tentang definisi bimbingan konseling, serta dapat memberikan program bimbingan konseling sebagai upaya untuk pembentukan karakter. Sebab hal itu harus diupayakan dalam menjalankan fungsi sebagai guru bimbingan konseling di sekolah. Sehingga guru bimbingan konseling dapat mencapai tujuan pelayanan bimbingan konseling dalam menanamkan nilai-nilai kekristenan.